BMI and adiposity based approach to obesity: the need for ethnic specificity. A reply to Kapoor et al. (2019). Issue 4 (4th April 2019) - Kryst, Łukasz; Żegleń, Magdalena; Wronka, Iwona; Woronkowicz, Agnieszka; Bilińska-Pawlak, Inez; Das, Rituparna; Saha, Rana; Das, Sukanta; Dasgupta, Parasmani
Abstract: The ethnicity of the studied group is one of the key characteristics that should be taken into consideration when analysing the problem of overweight and obesity. It is especially crucial in populations of countries such as India, where the proportion of the fat to lean mass and general adiposity are significantly different from those observed among Europeans. This can cause a higher risk of various metabolic-related diseases to appear at relatively lower absolute adiposity. Therefore, there is a need for further research regarding the issues of body mass and composition in Indian populations, to obtain additional information as well as to develop ethnically specific cut-off points.